Abrindo brechas na Igreja: Disputas e consensos em torno da leitura feminista da bíblia - Cruz, Jonas Santos (2017)
The aim of this research is to investigate the articulation between feminism and religion in the context of the feminist group Agar theology. It was used a qualitative methodology anchored in the observation of meetings and events carried out by the group, as well as in interviews with women who make up the group. The concept of secularization is used to understand the changes brought about in the field of religions, which led to the emergence of a religious pluralism. It was through secularization that changes arose in the Catholic Church, bringing the faithful's search for social justice and the institution's official discourse closer. This created a fertile ground for the emergence of politically engaged religious movements, such as the Christianity of li beration, which enabled the emergence of feminist theology in Brazil. The women who make up the Hagar worked in the Christianity of liberation, but they perceived innumerable aspects that led to its weakening, as the devaluation of the guidelines linked to the movements of women. The Center for Biblical Studies (CEBI) stands out as an organization that is embedded in liberation Christianity but has embraced a feminist reading of the Bible, which was a key element for Hagar to emerge and develop. In adhering to the reflections made by other Brazilian feminist theologians, Hagar uses the term deconstruction, originated from the discussions about gender and, in the context of feminist theology, is used to question epistemologically theological knowledge, as well as the Bible and its interpretations. These questions produced by the Hagar women have created tensions between the group and the CEBI, involving disputes over classifications about biblical and theological knowledge, and the creation of a specific space for feminist women.